2022
DOI: 10.3389/fphar.2021.816477
|View full text |Cite
|
Sign up to set email alerts
|

β-Sitosterol Inhibits Rheumatoid Synovial Angiogenesis Through Suppressing VEGF Signaling Pathway

Abstract: Background: Rheumatoid arthritis (RA) is a chronic disabling inflammatory disease that causes synovial angiogenesis in an invasive manner and leads to joint destruction. Currently available pharmacotherapy for RA has unwanted side effects and limitations. Although anti-angiogenic therapy is regarded as a new potential treatment for RA, only a few anti-angiogenic drugs are available. An increasing number of studies have shown that β-sitosterol (BSS) may exert inhibitory effects against angiogenesis. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…We obtained the ingredients and target information from database and constructed the ingredient‐ target network, with the major active components being beta‐sitosterol, stigmasterol, kaempferol, luteolin, and formononetin, the former two of which belong to the family of phytosterols, similar to cholesterol in structure and present in plant cell membranes. Many studies have reported that they offer anti‐inflammatory, antidiabetic and antioxidative benefits (Bao et al., 2022; Pei et al., 2022; Qian et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We obtained the ingredients and target information from database and constructed the ingredient‐ target network, with the major active components being beta‐sitosterol, stigmasterol, kaempferol, luteolin, and formononetin, the former two of which belong to the family of phytosterols, similar to cholesterol in structure and present in plant cell membranes. Many studies have reported that they offer anti‐inflammatory, antidiabetic and antioxidative benefits (Bao et al., 2022; Pei et al., 2022; Qian et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Qian et al's research showed that β -sitosterol could inhibit synovial angiogenesis by affecting the proliferation and migration of endothelial cells, thus reducing joint swelling and cartilage damage in CIA mice. It can inhibit the expression of the VEGF signaling pathway, slow joint inflammation, and improve the damage of bone and cartilage [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…β-Sitosterolis has already reported the improvement in RA by VEGF pathway. [40] By lowering MMP-8 secretion and synthesis, Stigmasterol therapy is said to ameliorate joint-related pathology to levels close to normal. This drop in the levels of metalloproteinase MMP-8 and inflammatory mediators is most likely brought on by a decrease in the activity of the transcription factors MAPKs and NF-kBp65.…”
Section: Discussionmentioning
confidence: 99%